Efficacy of outer membrane permeabilization in promoting aromatic isothiocyanates-mediated eradication of multidrug resistant Gram-negative bacteria and bacterial persisters - Lo, Chung-Cheng; Yeh, Tzu-Hui; Jao, Ya-Hsuan; Wang, Tzu-Hui; Lo, Horng-Ren (Folia microbiologica, 2024)
Multidrug resistant (MDR) bacteria are recognized to be one of the most important problems in public health. The outer membrane permeability is a critical intrinsic mechanism of bacterial resistance. In addition, bacteria produce a small number of dormant persister cells causing multidrug tolerance that reduces antimicrobial efficacy. This study aimed to evaluate the inhibitory effects of the combination of aromatic isothiocyanates (ITCs) with membrane-active agents on bacterial persisters and MDR Gram-negative bacteria. Our study demonstrated that membrane-active agents, particularly ethylenediaminetetraacetic acid (EDTA) synergistically enhanced the inhibitory activity of aromatic benzyl ITC and phenethyl ITC against most Gram-negative bacteria strains with fractional inhibitory concentration index values ranging from 0.18 to 0.5 and 0.16 to 0.5, respectively, and contributed to an 8- to 64-fold minimal inhibitory concentration reduction compared with those of aromatic ITCs alone. The EDTA-aromatic ITCs combination effectively reduced the survival rates of tested bacteria and significantly eradicated bacterial persisters (p = 0.033 and 0.037, respectively). The growth kinetics analysis also supported the enhanced inhibitory effect of EDTA-aromatic ITCs combination against tested bacteria. Our results suggested an alternate treatment strategy against Gram-negative bacteria, promoting the entry of aromatic ITCs into bacterial cytoplasm to facilitate bacterial clearance and thus preventing the development of bacterial resistance.
Keywords: vnější bakteriální membrána; Cell Membrane Permeability; Edetic Acid; mikrobiální testy citlivosti; Isothiocyanates; mikrobiální viabilita; permeabilita buněčné membrány; Gram-Negative Bacteria; EDTA; isothiokyanatany; Anti-Bacterial Agents; Microbial Sensitivity Tests; gramnegativní bakterie; Microbial Viability; Drug Synergism; mnohočetná bakteriální léková rezistence; synergismus léků; Drug Resistance, Multiple, Bacterial; Bacterial Outer Membrane; antibakteriální látky